IMPLEMENTASI MODEL PEMBELAJARAN BERDASARKAN MASALAH UNTUK MENINGKATKAN PROSES PEMBELAJARAN IPS SISWA KELAS IV SD NEGERI 153 PEKANBARU - Shinta Ramahi Ramahi; Lazim '; Eddy Noviana Noviana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The problems of this research is the low of learning process in Social studies. The low learning result was found at 4th grade of SD Negeri 153 Pekanbaru because the teacher was lack in doing learning process and teacher also didn't apply the learning model in teaching Social. Based on the problems, the alternative way is using appropriate learning model in students' encironment. Problem based learning gives students an opportunity to solve the problem and connect the learning activity in their daily life. The aims of this research is to improve the learning process and the result of Social studies score for 4th grade students of SD Negeri153 Pekanbaru. This research was classroom action research. The sample of this research was 4th grade of SD Negeri 153 Pekanbaru which the total 38 students. The result of the research can be seen in teachers' mean score in 1st cycle which was 60% in Mediocare category . It improved about 10% to 70% in Good category. The 2nd cycle improved to 80% in Good then from 5% to 85% in exellentcategory. Students activity in the 1st cycle had 55% in good category of mean score improved 10% to 65% in good category. In the 2nd cycle, the mean score was 75% in good category improved 10% to 85% in excellent. Data of students acore also had the improvement before the application problem based learning only 16 students could pass the standart score (42,10%) and their mean was 64.31. The improvement in 1ts cycle was 24 students (63.15%) could pass with their mean score was 75.57. The 2nd cycle improved into 33 students (86.64%) with the mean score was 81.57. The total improvement of students score was 26.83%. According to the result, it can be concluded that hypothesis of the application problem based learning can improve the process of social learning for 4th grade students of SD Negeri 153 Pekanbaru. Keywords : Problem based learning and learning process